Consider H. Willett, Laws and Ordinances Governing the Village of Hyde Park 61, § 6 (1876) - (:unkn) unknown (My University, 1876)
§ 6: Prohibited shooting any bird or animal, hunting with a gun or dog in any street, alley, thoroughfare, park, or public grounds.
Keywords: HUNTING REGULATION